2008
DOI: 10.1007/s10194-008-0026-x
|View full text |Cite
|
Sign up to set email alerts
|

The primary headaches: genetics, epigenetics and a behavioural genetic model

Abstract: The primary headaches, migraine with (MA) and without aura (MO) and cluster headache, all carry a substantial genetic liability. Familial hemiplegic migraine (FHM), an autosomal dominant mendelian disorder classified as a subtype of MA, is due to mutations in genes encoding neural channel subunits. MA/MO are considered multifactorial genetic disorders, and FHM has been proposed as a model for migraine aetiology. However, a review of the genetic studies suggests that the FHM genes are not involved in the typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 179 publications
(115 reference statements)
1
32
0
1
Order By: Relevance
“…These modiWcations decrease (or increase) gene expression and thus inXuence molecular pathways (Jirtle and Skinner 2007). Epigenetic eVects occur in early development but may change over lifetime, by lifestyle and diet, and it has been suggested that changes for instance in development of the individual or triggers such has stress determine the 'epigenetic outcome' and thus may aVect migraine susceptibility (Montagna 2008). It would be interesting to subgroup migraine patients for genetic and/or epigenetic studies according to their self-reported triggers.…”
Section: Some Thoughts On Epigenetic and Trigger Mechanisms In Genetimentioning
confidence: 99%
“…These modiWcations decrease (or increase) gene expression and thus inXuence molecular pathways (Jirtle and Skinner 2007). Epigenetic eVects occur in early development but may change over lifetime, by lifestyle and diet, and it has been suggested that changes for instance in development of the individual or triggers such has stress determine the 'epigenetic outcome' and thus may aVect migraine susceptibility (Montagna 2008). It would be interesting to subgroup migraine patients for genetic and/or epigenetic studies according to their self-reported triggers.…”
Section: Some Thoughts On Epigenetic and Trigger Mechanisms In Genetimentioning
confidence: 99%
“…9 Although there are numerous studies reporting that homocysteine is associated with migraine headaches, for example, [10][11][12] there is only 1 study describing the interference of MTHFR with ocular accommodation. 13 FIGURE 1.…”
Section: Discussionmentioning
confidence: 98%
“…Однако вы-явление цитокинового дисбаланса у больных ПГБ, не имеющих клинических признаков им-мунных расстройств, позволяет предположить, что у ряда пациентов имеется доклиническая ста-дия иммунопатологии, либо цитокины выступа-ют в качестве самостоятельных патогенетических факторов цефалгий. Как причина цитокинового дисбаланса рассматриваются генетические осо-бенности [23], лекарственный абузус [22], стресс и депрессия [19].…”
Section: карпова ми и др медицинская иммунологияunclassified